ASSESSMENT OF COMMUNITY COUNSELLING STRATEGIES IN RURAL AGRIPRENEURSHIP DEVELOPMENT IN GOMBE STATE, NIGERIA - Baba, M. M.; Saleh, A.; Umaru, B. Y.; Ahmad, M. E.; Mudathir, A. (Journal of Agripreneurship and Sustainable Development, 2019)
The study examined the community counselling strategies for rural agro-entrepreneurship development in Gombe State, Nigeria. A three-stage sampling technique was used to select 186 community counselors, rural extension workers and entrepreneurs from the three Local Government Areas of the State. Data were collected using structured questionnaire and were subjected to descriptive statistics such as; the means, standard error and mean decision on a 5-point Likert scale rating for analysis. The result revealed that, majority of the perceived roles of community counselors in agro-entrepreneurship development in the study area was accepted. Implying that, rural counselors and extension workers have significantly contributed to agro-entrepreneurship and sustainable economic development in the study area. Also, the results revealed that, most of the perceived factors for effective implementation of rural agro-entrepreneurship programmes in the study area were significant. Furthermore, the findings of the study revealed the mean score of all the perceived counselling skills and strategies to be ≥ 3; meaning that the variables were significantly accepted. To achieve sustainable development in rural agripreneurship, the study recommends concerted efforts by the government in collaboration with various local and international agencies to provide more of agro-entrepreneurial capacity building programmes and other incentives to the rural communities.